(20R)-panaxadiol improves obesity by promoting white fat beigeing - Lv, Yuqian; Lv, Xiaoyan; Feng, Jianshu; Cheng, Fanghui; Yu, Zhiyi; Guan, Fengying; Chen, Li (Frontiers in Pharmacology, 2023)
Obesity is an important cause of a range of metabolic diseases. However, the complex mechanisms of obesity and its related diseases make some weight loss methods ineffective or have safety issues. Ginseng, a specialty of Jilin Province in China with both edible and medicinal value, contains mainly ginsenosides and other components. In order to study the anti-obesity effect of ginseng, network pharmacology was used to predict and screen the active ingredients, action targets and signaling pathways of ginseng. We found 20R-Panaxadiol (PD) is a more desirable active ingredient due to its high drug-like properties and high bioavailability. Moreover, it is closely related to cAMP pathway which is more important in metabolism regulation. The corresponding pharmacodynamic targets of PD include ADRB2 (the gene encoding the β2-adrenoceptor receptor). Our study aimed to investigate whether Panaxadiol can promote white adipocyte beigeing and increase thermogenesis through modulating the β2/cAMP pathway to exert anti-obesity effects. The results of this study demonstrated that PD significantly reduced body weight, improved glucose tolerance and lipid levels in high-fat-induced obese mice and genotypically obese mice(ob/ob), and also reduced lipid droplet size in PA-treated hypertrophic adipocytes in vitro. Molecular biology assays confirmed that cAMP response element binding protein（CREB）phosphorylation was increased after PD administration, and the expression of thermogenesis-related proteins UCP1, PRDM16 and mitochondrial biosynthesis-related proteins PGC-1α, TFAM and NRF1 were increased. Molecular docking results showed a low binding energy between β2 receptors and PD, indicating an affinity between the β2 receptor and PD. In addition, the β2 receptor inhibition, reversed the anti-obesity effect of PD on the body weight, lipid droplets, the expression of thermogenesis-related proteins and CEEB phosphorylation in ob/ob mice. These results suggest that PD may promote the expression of thermogenic proteins through phosphorylation of CREB via β2 receptor activation, and thus exert anti-obesity effects.